Analysis of Instagram Content Design for the Visual Promotion of Kopi Bengkong, a Micro, Small, and Medium Enterprise Coffee Product - Afriliyani, Vika; Eko Sugiarto (Catharsis, 2024)
The rapid advancement of technology, particularly in information and communication technology (ICT), has significantly impacted various aspects of human life, including economic development. This shift has influenced global marketing trends, transitioning from conventional (offline) to digital (online) marketing. Digital marketing empowers potential buyers to access product information and conduct transactions online. This study aims to analyze how visual content design on Instagram can be utilized as an effective promotional medium for Kopi Bengkong, a local coffee product. This research employs a qualitative content analysis approach, focusing on the visual content components posted on the Instagram account @bengkong_coffee. Data collection methods include document study, literature review, and virtual observation. The findings indicate that creative and engaging visual content on Instagram can enhance brand awareness and audience engagement, thereby expanding the market reach for local coffee products.